(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
This descriptive type of cross-sectional study was conducted in MMCH and CBMCB during the period from 1st July/2005 to 30th Jun/2006.The aim of the study was to find out the prescribing pattern of antimicrobials in cough or cold and pneumonia in under five years children. Prescriptions were collected from the out-patient pediatric department by using structured questionnaire. The structured questionnaires were made according to WHO/ INRUD drug use indicator. In case of cough or cold, the main findings on drug use were (a) Average number of drugs per prescription were 3.21 in MMCH and 3.85 in CBMCB respectively, (b) Percentage of prescriptions with an antibiotic prescribed was 100% in MMCH and CBMCB, (c) Percentage of drugs prescribed in generic name were 57.69% in MMCH and it was nil in CBMCB, (d) Cotrimoxazole, Amoxicillin and Cephalosporin were used frequently in MMCH and Cephalosporin and Erythromycin mostly were used in CBMCB, and (e) Route of administration were appropriate in both the institutes. In case of pneumonia, (a) Average number of drugs per prescription were 3.77, (b) Percentage of prescription with an antibiotic was 100%, (c) Percentage of drug prescribed in generic name was 27.5%, (d) Cephalosporin were used mostly (45.5%) for the treatment of pneumonia. Trend of poly pharmacy was found in both the institutes DOI: http://dx.doi.org/10.3329/bjpp.v27i1-2.20069 Bangladesh J Physiol Pharmacol 2011; 27(1&2):13-20